Adaptive relay selection protocol for the parallel hybrid RF/FSO relay channel - Najafi Kalyani, Marzieh; Jamali Kooshkghazi, Vahid; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
Hybrid radio frequency (RF)/free space optical (FSO) systems are among the candidate enabling technologies for the next generation of wireless networks since they benefit from the advantages of both the FSO subsystem, e.g. high data rates, and the RF subsystem, e.g. high reliability in terms of link connectivity. In this paper, we focus on the problem of throughput maximization in the parallel hybrid RF/FSO relay channel. In the parallel hybrid RF/FSO relay channel, a source node sends its data to a destination node with the help of multiple relay nodes. Thereby, the source-relay and the relay-destination FSO links are orthogonal with respect to each other due to the narrow beam employed for FSO transmission whereas the RF links are half duplex with respect to each other due to the broadcast nature of RF signals. We derive the optimal relay selection policies for transmission and reception for the RF and FSO links and the optimal time allocation policy to the RF relay reception and transmission links. Simulation results demonstrate that a considerable gain can be achieved by the proposed adaptive protocol in comparison with benchmark schemes from the literature.<br
Keywords: Radio frequency; Relays; Optical Transmitters; Protocols; Throughput; RF Signals; Receivers